Synthesis, Crystal Structure and Insecticidal Activity of 1-[2-(3-Ethyl-2,2-dimethylcyclobutyl)acetyl]-3-o-tolylthiourea - Yin, Yan-Bai; Han, Jia; Zhang, Ya-Li; Song, Zhan-Qian; Liu, Tao (Asian Journal of Chemistry, 2014)
The compound 1-[2-(3-ethyl-2, 2-dimethylcyclobutyl)acetyl]-3-o-tolylthiourea has been synthesized and its structure was characterized by IR, 1H NMR and single crystal X-ray diffraction. The crystal belongs to monoclinic system, space group P21/c, a = 14.335(3) Å, b = 9.7100(19) Å, c = 26.737(5) Å, a = 90°, b = 92.70(3)°, g = 90°, V = 3717.5(13) Å3, Z = 4, μ = 0.178 mm-1, Dc = 1.138 g/cm3, F(000) = 1376, R = 0.0921, wR2 = 0.1379, formula unit C18H26N2OS. Present compound has a fragment of 2,2-dimethylcyclobutane and its conformation represents semi-chair. The intermolecular and intramolecular hydrogen bonds are revealed. Its insecticidal activity against Ostrinia furnacalis was also reported in this work.